Promoção de saúde e empoderamento: oficinas com jovens mães de Ermelino Matarazzo (Revista de Cultura e Extensão USP, 2009)
The main goal of this article is to discuss the strategies of health promotion and the empowerment of the participants of the project: Health Promotion’s workshop with youth 12 to 19 years. This is a project developed since November of 2006 in the Ermelino Matarazzo. The project began with the dual aim of expanding the training of students about health promotion and to meet the demands of the neighborhood of the University. The issue of early motherhood and the difﬁ culties experienced by young mothers in the neighborhood was identiﬁ ed as one of the needs of intervention. The project is coordinated by two professors and students of Escola de Artes, Ciências e Humanidades. The discussion presented refers to the years 2007 and 2008. The qualitative impacts and empowerment are often difﬁ cult to assess, but we can say that in the reports of participants is possible to observe signiﬁ cantly changes in the relationship with their peers, families and society in general.